2020
DOI: 10.1177/0265407520935193
|View full text |Cite
|
Sign up to set email alerts
|

Modeling multivariate associations with parental loneliness via perceived closeness and support

Abstract: Objectives: Recent research findings suggest the prevalence of loneliness is increasing in middle-aged adults parenting children, challenging the notion this demographic is typically at low risk of loneliness. Method: The current study applied the cognitive discrepancy model as theoretical foundation to investigate the variance of individual and situational variables contributing to perceived closeness and support and consequently loneliness. Structural equation modeling was employed to identify multivariate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…The COVID-19 crisis facilitated an examination of the potential role of psychological resilience in bolstering perceptions of support in a particularly vulnerable group, caregivers of children. The disruption in social support networks posed unprecedented challenges for parents, for whom there are considerable consequences such as loneliness, lack of perceived support, and psychological distress (Hall et al, 2020; Poppert Cordts et al, 2020). Based on four waves of data following the outbreak of the pandemic, we found that parents’ MER was associated with decreased loneliness and increased perceived social support later in time.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 crisis facilitated an examination of the potential role of psychological resilience in bolstering perceptions of support in a particularly vulnerable group, caregivers of children. The disruption in social support networks posed unprecedented challenges for parents, for whom there are considerable consequences such as loneliness, lack of perceived support, and psychological distress (Hall et al, 2020; Poppert Cordts et al, 2020). Based on four waves of data following the outbreak of the pandemic, we found that parents’ MER was associated with decreased loneliness and increased perceived social support later in time.…”
Section: Discussionmentioning
confidence: 99%
“…Several independent variables were explored as being factors that were potentially related to loneliness from an ecological systems model [ 14 ]. These variables were selected based on literature reviews of previous studies [ 4 – 9 , 15 21 ] and 3 focused group interviews with 41 professionals or community volunteers, and 31 one-to-one interviews with mothers raising children less than 3 years of age.…”
Section: Study Variablesmentioning
confidence: 99%
“…However, in contrast to desired emotional closeness, loneliness also captures psychological distress about having perceived difficulty obtaining social connection. Notably, whereas desired emotional closeness is negatively associated with depression and positively associated with perceived emotional closeness (Flores & Berenbaum, 2014), loneliness is positively related to depression (Cacioppo et al., 2006) and negatively associated with perceived emotional closeness (Hall et al., 2020). Desired emotional closeness may also demonstrate an opposite pattern in social circuitry (i.e., greater activation) in response to negative social images with relevance to adaptive functioning.…”
Section: Introductionmentioning
confidence: 99%